The location of magnetic reconnection at Saturn's magnetopause: A comparison with Earth. Issue 4 (4th April 2014) - Fuselier, S. A.; Frahm, R.; Lewis, W. S.; Masters, A.; Mukherjee, J.; Petrinec, S. M.; Sillanpaa, I. J.
Abstract Data from the Cassini Electron Spectrometer are used to investigate the location of magnetic reconnection at Saturn's magnetopause. Heated, streaming electron distributions in the boundary layer on the magnetosheath side of the magnetopause are evidence of reconnection and an open magnetopause. A model for the location of reconnection is used to compare the modeled and observed streaming direction of the heated electron distributions. Magnetic reconnection at Saturn's magnetopause is predicted and observed to occur at locations similar to those at Earth's magnetopause. Although not conclusive, the results here are consistent with the expected importance of X‐line drifts in suppressing low‐shear reconnection. Because of different conditions at Saturn's magnetopause, this suppression is predicted to be more severe at Saturn than at Earth.